CUTTING OPTIMIZATION LUMBER ON BLANKS FOR PARQUET BOARDS - Rykunin, Stanislav; Kulikova, Nadezhda (Innovation in Woodworking Industry and Engineering design, 2012)
The most common malformations of birch are knots, rot, and the curvature of the false nucleus. False heartwood not allowed in the blanks always without any restrictions. This area has a low permeability of the wood, the tensile strength along the fiber toughness. In birch false core easily crack. False heartwood is resistant to rot less than the sapwood. Since the size of the false nucleus depends on the age of trees, it follows that the diameter between the diameter of sawlogs and heartwood correlation exists. Using data from the bulkhead material was determined by the dependence of the diameter of the heartwood of the diameter of sawlogs in the butt. The experimental results showed that with decreasing length of the assortment of „n“ time deflection also decreases by about a „n“ time, that is, the value of the curvature of the assortment, expressed in % change of its length remains virtually unchanged. In this case, increase the yield of blanks can individual approach to cutting of timber.